2010
DOI: 10.1177/1352458510376177
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB1*1501 intensifies the impact of IL-6 promoter polymorphism on the susceptibility to multiple sclerosis in an Iranian population

Abstract: We suggest more studies to confirm these results in other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
10
2
Order By: Relevance
“…Interestingly, the decrease was not seen in patients with PP-MS. Our results are in striking contrast to those of both Shahbazi et al , who found an increased risk for MS associated with the G allele of −174 in an Iranian cohort [11], and of Mirowska-Guzel et al , who found increased risk of MS to be associated with the C allele of −174, particularly with the CC genotype in a Polish cohort [10]. Whether these differences are due to differences in the ethnicity of the populations, or to some other factor, remains to be determined.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Interestingly, the decrease was not seen in patients with PP-MS. Our results are in striking contrast to those of both Shahbazi et al , who found an increased risk for MS associated with the G allele of −174 in an Iranian cohort [11], and of Mirowska-Guzel et al , who found increased risk of MS to be associated with the C allele of −174, particularly with the CC genotype in a Polish cohort [10]. Whether these differences are due to differences in the ethnicity of the populations, or to some other factor, remains to be determined.…”
Section: Resultscontrasting
confidence: 99%
“…[10] 228 MS and 193 controls; Shahbazi et al . [11] 345 MS and 426 controls; Mihailova et al . [9] 55 MS and 86 controls; Fedetz et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HLA is the most informative genetic system known to date (1).Several researchers have focused on HLA as a potential risk allele in the pathogenesis of some diseases (2)(3)(4). On the other hand, HLA polymorphism is kind of epidemiological risk factor for some diseases.…”
Section: Introductionmentioning
confidence: 99%